Artificial Knee Joint and Ski Load Simulator for the Evaluation of Knee Braces and Ski Bindings. (2016) - Nusser, Michaela; Hermann, Aljoscha; Senner, Veit
Abstract: Introduction: Epidemiological studies show that severe knee injuries are prevalent in alpine skiing. Their incidence is related to ski boot and ski binding concept – both designed to prevent tibia fractures. To reliably protect the knee, ski bindings need a release mechanism which follows different release principles. Therefore, attempts are made to develop mechatronic concepts implementing additional criteria and to release the foot when critical loads at the knee are reached. One possibility to systematically manipulate external loads and to investigate the resulting stresses in the joint are experiments using an artificial leg. This paper describes the development and the evaluation of such kind of model ("leg surrogate") including a complex artificial knee joint. The evaluation includes tests concerning the reliability, sensitivity and plausibility of the surrogate. Method: Tibia and femur consist of an aluminum bone imitate and are reconstructed based on human computerized tomography data. Human endoprosthesis are used as articulating surfaces for the tibial plateau, the femoral condyles, the trochlea as well as the patella. Ten steel ropes connected to a force measuring cell are incorporated simulating the muscle. The muscle volume is imitated by a three layer coat of thermoplastic. The artificial knee ligaments are instrumented with custom made elongation and force sensors. Leg surrogate presetting's can be varied trough the knee angle, hip angle, varus or valgus position, tension of the muscle and pretension of the ligaments. A test rig enables t quasi static application of external loads to the leg surrogate in any combination about the x, y and z-axis. Results: The leg surrogate delivers reproducible measurements with a maximum variation of 2.7%. It allows to simulate different conditions like muscle tension or hip angles and to record their influence on the knee ligaments. The plausibility checks performed indicate, that the leg surrogate represents the behavior of the human knee to a large extend. Conclusion: The new leg surrogate allows to simulate not only alpine skiing injury but also other load situations. It therefore can be used to systematically investigate critical load situations to the knee and the prevention effect of safety devices such as mechatronic ski bindings or knee protection devices like preventive knee braces.